ANALISIS YURIDIS TENTANG PEMBUBARAN DAN LIKUIDASI (PENYELESAIAN) ATAS PAILITNYA KOPERASI - ASPIN ARUAN (PREMISE LAW JURNAL, 2013)
ABSTRACT The legal consequence of the liquidation of cooperative is that its legal entity status continues to exist before its liquidation is registered in the Indonesian National Gazette. Cooperative cannot take legal action unless it is necessasry to settle the assets of the liquidated cooperative, the cessation must be followed with liquidation, the cooperative business is terminated unless it is for liquidation, the authority of administrator and supervisor is deactivated, the authority of administrator is taken over by the liquidator, “the cooperative is under liquidation/settlement”, once the agreement has been run can be terminated, the members of cooperative are no longer allowed to resign. Legally, the distribution of the assets of liquidated cooperative is done by taking action of settlement including listing and collecting the assets of the cooperative, verifying the debt of the cooperative, determining the procedures of distributing the assets of liquidated cooperative, paying the creditor with paying attention to law of guarantee and determining the creditor scale of priority, paying the remaining assets of liquidation proceeds to the members of cooperative capital certificate holders. Keywords: Deactivation, Liquidation/Settlement, Cooperative